Linear combinations of squares

How many pairs of integers (not necessarily positive) are there such that both a 2 + 6 b 2 a^2+6b^2 and b 2 + 6 a 2 b^2 + 6a^2 are both squares?

This problem is proposed by Shivang .

Details and assumptions

You may choose to read the post on Gaussian Integers .

You may submit original proposed problems to [email protected].


The answer is 1.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

11 solutions

Qi Huan Tan
May 20, 2014

Clearly, ( a , b ) = ( 0 , 0 ) (a,b)=(0,0) is a solution. Assume a , b 0 a,b\neq0 . Let a 2 + 6 b 2 = x 2 , b 2 + 6 a 2 = y 2 a^2+6b^2=x^2 , b^2+6a^2=y^2 . Adding them yields 7 ( a 2 + b 2 ) = x 2 + y 2 7(a^2+b^2)=x^2+y^2 . 7 7 divides x 2 + y 2 x^2+y^2 . The quadratic residue modulo 7 are 0,1,2,4. Therefore, both x 2 x^2 and y 2 y^2 are divisible by 7. Since 7 is a prime, 7 x 7|x and 7 y 7|y . Let x = 7 x 1 x=7x_1 and y = 7 y 1 y=7y_1 . 7 ( a 2 + b 2 ) = ( 7 x 1 ) 2 + ( 7 y 1 ) 2 7(a^2+b^2)=(7x_1)^2+(7y_1)^2 , a 2 + b 2 = 7 ( x 1 2 + y 1 2 ) a^2+b^2=7(x_1^2+y_1^2) . This process will repeat indefinitely if a a and b b are not equal to 0 ( a 2 + b 2 a^2+b^2 will approach infinity), a contradiction.

Fermat's theorem on sum of two squares which states that a number is expressible as a sum of 2 squares if and only if in the prime factorization, every prime of the form 4 k + 3 4k+3 occurs an even number of times.

Mistakes

  1. Do NOT divide by 0. When you divide by an algebraic expression, make sure that you state the cases where it is equal to 0, and deal with them separately.

  2. "Since the problem do not specify that a 2 + 6 b 2 6 a 2 + b 2 , a^2 + 6b^2 \neq 6a^2 + b^2, then we can assume that a 2 + 6 b 2 = 6 a 2 + b 2 a^2 + 6b^2 = 6a^2 + b^2 ".

Calvin Lin Staff - 7 years ago

Log in to reply

Why does the assumption list recommend reading "Gaussian integers"??

Eddie The Head - 7 years ago
Adetunji Ajimakin
May 20, 2014

Let us assume that there exists a pair of integers (x,y) that satisfies these conditions and

x 2 + 6 y 2 = p 2 x^2 + 6y^2 = p^2 ------(1)
y 2 + 6 x 2 = q 2 y^2 + 6x^2 = q^2 _ ------(2)
where x, y, p, q \in Z {Z}
(1)+(2) gives
_


x 2 + y 2 + 6 y 2 + 6 x 2 = p 2 + q 2 x^2 + y^2 + 6y^2 +6x^2 = p^2 + q^2

Karolina Patsios
May 20, 2014

If we add both expressions we have: 7(a^2+b^2)=c^2+d^2

Left side is a multiple of 7 and Right side must be a multiple of 7 for a solution to exist.

Both c and d can be expressed as 7k, 7k+1, 7k+2, 7k+3, 7k+4, 7k+5, 7k+6.

So, remainder when (c^2+d^2) is divided by 7 can be the same if one among the following is divided by 7:

0, (1+2^2), (1+3^2), (1+4^2), (1+5^2), (1+6^2)

(2^2+3^2), (2^2+4^2), (2^2+5^2), (2^2+6^2)

(3^2+4^2), (3^2+5^2), (3^2+6^2)

(4^2+5^2), (4^2+6^2)

(5^2+6^2)

None of the above except 0 is divisible by 7.

So, only one solution exist (a,b) = (0,0)

http://www.jiskha.com/display.cgi?id=1361896602

Calvin Lin Staff - 7 years ago

Hahahaha... ;)

Shaan Vaidya - 7 years ago
Dicky Afrizal
May 20, 2014

a^2 + 6b^2 = x^2 6a^2 + b^2 = y^2 a^2 + 6b^2 + 6a^2 + b^2 = 7a^2 + 7b^2 = x^2 + y^2 then mod 7 only one possible remainder is 0 so the solution is 1

Mursalin Habib
May 19, 2014

Let

a 2 + 6 b 2 = c 2 ( 1 ) a^2+6b^2=c^2\cdots (1) b 2 + 6 a 2 = d 2 ( 2 ) b^2+6a^2=d^2\cdots(2)

where c c and d d are integers.

If you add up ( 1 ) (1) and ( 2 ) (2) , you'll get:

7 ( a 2 + b 2 ) = c 2 + d 2 ( 3 ) 7(a^2+b^2)=c^2+d^2\cdots(3)

So our question becomes, how many integer solutions are there for equation ( 3 ) (3) . That shouldn't be hard, because we have reduced the problem to another problem that we already solved :)

( 0 , 0 , 0 , 0 ) (0,0,0,0) is the only integer solution.

If a , b , c , d a, b, c, d are all non-zero integers then ( 3 ) (3) has no solution.

Here's the proof.

Consider the solution ( a , b , c , d ) (a, b, c, d) such that c 2 + d 2 c^2+d^2 is as small as it can be.

Notice that 7 ( c 2 + d 2 ) 7|(c^2+d^2) .

You can do a little case-work [consider the qudratc residues modulo 7 7 ] and see that this means 7 c 7|c and 7 d 7|d .

Let c = 7 k 1 c=7k_1 and d = 7 k 2 d=7k_2 .

Then rewrite ( 3 ) (3) as

7 ( a 2 + b 2 ) = 49 ( k 1 2 + k 2 2 ) 7(a^2+b^2)=49({k_1}^2+{k_2}^2) 7 ( k 1 2 + k 2 2 ) = a 2 + b 2 \Rightarrow 7({k_1}^2+{k_2}^2)=a^2+b^2

Notice that this new equation is the same as ( 3 ) (3) . The only difference is that now ( a 2 + b 2 ) (a^2+b^2) acts as ( c 2 + d 2 ) (c^2+d^2) . It's not hard to see that ( a 2 + b 2 ) < ( c 2 + d 2 ) (a^2+b^2)<(c^2+d^2) . But that is a contradiction! Remember that we made ( c 2 + d 2 ) (c^2+d^2) as small as possible. But now we have a new ( c 2 + d 2 ) (c^2+d^2) that is less than that.

We arrived at this contradiction by assuming that the set of non-zero solutions to ( 3 ) (3) is non-empty. So that has to be false.

So, there are no more solutions. ( a , b ) = ( 0 , 0 ) (a, b)=(0,0) is the only solution.

And the answer is 1 \boxed{1} .

Gilbert Simmons
May 28, 2014

If a 2 + 6 b 2 a^2 + 6b^2 is a square then b b cannot be odd - if it was, a 2 + 6 b 2 a^2 + 6b^2 would be equivalent to 2 or 3 mod 4, which is impossible if the result is to be a square itself (i.e. 0 or 1 mod 4).

By the same argument if 6 a 2 + b 2 6a^2 + b^2 is a square then a a cannot be odd. Therefore we can assume that a , b a, b and hence the squared result, are all even.

Therefore the equations a 2 + 6 b 2 = x 2 a^2 + 6b^2 = x^2 and 6 a 2 + b 2 = y 2 6a^2 + b^2 = y^2 can both be divided through by 4 to create a two new expressions that have the same property, i.e. all three squares are even.

Repeated division by 4 must eventually make one or more of the squares odd, contradicting our assumption that the squares are all even, unless they are all zero.

Siddharth Kumar
May 22, 2014

Quite easily solved by infinite descent.

Marek Bernat
May 20, 2014

Denote the implicit squares in the problem as a 2 + 6 b 2 = n 2 a^2 + 6b^2 = n^2 and b 2 + 6 a 2 = m 2 . b^2 + 6a^2 = m^2. Adding the equations, we obtain 7 ( a 2 + b 2 ) = n 2 + m 2 . 7 (a^2 + b^2) = n^2 + m^2. Now, consider a + i b a+ib and n + i m n+im as elements of Gaussian integers. Then the above equation tells us that the norms squared of these elements differ by factor of 7 7 . Since unique factorization holds in Gaussian integers, this implies that n + i m n+im is divisible by an element of norm 7 \sqrt{7} . But this is not possible since 7 = c 2 + d 2 7 = c^2 + d^2 cannot hold. Both c c and d d would need to be smaller than 3 3 and then the only possibilities are 0 2 + 1 2 = 1 0^2 + 1^2 = 1 , 0 2 + 2 2 = 4 0^2 + 2^2 = 4 and 1 2 + 2 2 = 5 1^2 + 2^2 = 5 . So we have derived a contradiction whenever a 2 + b 2 a^2 + b^2 is non-zero. There is however no problem with a = b = 0 a = b = 0 , and so the answer is 1 \bf 1 .

Argh, I forgot to mention the case 1 2 + 1 2 = 2 1^2 + 1^2 = 2 . It does not change anything though.

Marek Bernat - 7 years ago
Adrian Mendizabal
May 20, 2014

Let integer k k be a perfect square such that for any integer n n : k = n 2 k = n^2 .

Also, a , b I a,b \in I

From the problem,

a 2 + 6 b 2 = k 1 a^2 + 6b^2 = k_1 ; ( 1 ) (1)

6 a 2 + b 2 = k 2 . 6a^2 + b^2 = k_2. ; ( 2 ) (2)

We know that k i k_i can only a perfect square integer as in:

k i k_i \in [ 0 , 1 , 4 , 9 , 25 , 36... ] [0, 1, 4, 9, 25, 36...]

Since the problem do not specify that k 1 k 2 , k_1 \neq k_2, then we can assume that k 1 = k 2 k_1 = k_2 , or k i = k i + 1 k_i=k_{i+1}

If k 1 = k 2 , k_1 = k_2,

a 2 + 6 b 2 = 6 a 2 + b 2 a^2 + 6b^2 = 6a^2 + b^2 ; ( 3 ) (3)

then,

5 b 2 5 a 2 = 0 5b^2 - 5a^2 = 0 ; ( 4 ) (4)

Essentially, this will yield a result:

a = b a=b , ( 5 ) (5)

If we assume that a general perfect square for both eqn. 1 and eqn. 2 to be equal,

k i = k i + 1 k_i = k_{i+1} ; ( 6 ) (6)

We can substitute eqn. 5 and 6 to eqn. 1, we get:

a 2 + 6 a 2 = k i a^2 + 6a^2 = k_i ; ( 7 ) (7)

Applying the necessary algebraic operations,

7 a 2 = k i 7a^2 = k_i ; ( 8 ) (8)

Then,

a 2 = k i 7 a^2 = \frac {k_i}{7} ; ( 9 ) (9)

This yields to a general equation,

a = b = ± k i 7 a = b = \pm \sqrt{\frac {k_i}{7}} ; ( 10 ) (10)

We know k i [ 0 , 1 , 4 , 9 , 25 , 36... ] k_i \in [0, 1, 4, 9, 25, 36...]

By substituting values of k i k_i in eqn. 10, we only get one integer ordered pair of ( a , b ) (a,b) , and that is when k i = 0 k_i = 0 . The rest are non-integer ordered pairs.

The only integer value of ( a , b ) (a,b) \to ( 0 , 0 ) (0,0) .

So only 1 1 ordered pair for can be a solution.

Jaydutt Kulkarni
May 20, 2014

Let k,m be any 2 integers belonging to Z Let a 2 + 6 b 2 = k 2 a^2 + 6*b^2 = k^2 ....(1) 6 a 2 + 36 b 2 = 6 k 2 \Rightarrow 6*a^2 + 36*b^2 = 6*k^2 ......(2) Let 6 a 2 + b 2 = m 2 6*a^2 + b^2 = m^2 ......(3) 36 a 2 + 6 b 2 = 6 m 2 \Rightarrow 36*a^2 + 6*b^2 = 6*m^2 ....(4) Subtracting (3) from (2) and (1) from (4) we get 35 b 2 = 6 k 2 m 2 35*b^2=6*k^2-m^2 35 a 2 = 6 m 2 k 2 35*a^2=6*m^2-k^2 Taking ratio we get ( a 2 / b 2 ) = ( 6 k 2 m 2 ) / ( 6 m 2 k 2 ) \Rightarrow (a^2/b^2) = (6*k^2-m^2 )/(6*m^2-k^2 ) By Componendo-Dividendo ( a 2 + b 2 ) / ( a 2 b 2 ) = ( 5 m 2 5 k 2 ) / ( 7 m 2 7 k 2 ) ( a 2 + b 2 ) / ( a 2 b 2 ) = 5 / 7 7 a 2 + 7 b 2 = 5 a 2 5 b 2 a 2 = 6 b 2 (a^2 + b^2)/(a^2 - b^2) = (5*m^2-5k^2)/(7*m^2-7k^2) \Rightarrow (a^2 + b^2)/(a^2 - b^2) = 5/7 \Rightarrow 7*a^2 + 7*b^2 = 5*a^2 - 5*b^2 \Rightarrow a^2 = -6*b^2 No integer solution exists except for (0,0) So only 1 pair exists

Alex Newman
May 20, 2014

Proof: From the problem we have that a^2+6b^2 and b^2+6a^2 equal some squares, lets name them c^2 and d^2 respectively. Thus we have a^2+6b^2=c^2 and b^2+6a^2=d^2.

We then add the two expressions, producing 7a^2+7b^2=c^2+d^2 =>7(a^2+b^2)=c^2+d^2 we now observe that c^2+d^2 must be divisible by 7.
c and d can be written as congruences mod 7. thus, 7n, 7n+1, 7n+2, 7n+3, 7n+4, 7n+5, 7n+6

since we can rewrite c and d in this way, the only thing required to check for divisibility by 7 is the remainder.

If you are wondering why we only need to check the remainders for divisibility by 7. look at this more general case.
take c=7n+x (0<=x<=6) c^2=(7n+x)^2= 49n^2+14nx+x^2 49n^2 is obiously divisible by 7, as well as 14nx. The only question arises from x^2, the remainder.

so we check these cases for divisibility. (0^2+0^2) (1^2+2^2), (1^2+3^2), (1^2+4^2), (1^2+5^2), (1^2+6^2) (2^2+3^2), (2^2+4^2), (2^2+5^2), (2^2+6^2) (3^2+4^2), (3^2+5^2), (3^2+6^2) (4^2+5^2), (4^2+6^2) (5^2+6^2) the only choice that works is (0^2+0^2) thus the only pair that satisfy this property is a,b=(0,0)

http://www.jiskha.com/display.cgi?id=1361896602

Calvin Lin Staff - 7 years ago

the answer should be 4. since it's mentioned that its not necessarily positive

Rishi Jain - 6 years, 10 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...